Analisa Rancangan Desain Antarmuka Aplikasi LibrarySense Menggunakan System Usability Scale - Jatmiko, Gagas Pradipta; Suputra, I Putu Gede Hendra (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 1 (2024): JNATIA Vol. 3, No. 1, November 2024DO - 10.24843/JNATIA.2024.v03.i01.p16, 2024)
The comfort of the library plays a crucial role in supporting learning activities. Temperature that is too hot or too cold, high levels noise, or the presence of smoke can affect the focus and effectiveness of learning for library users. LibrarySense is an application that utilizes wireless sensor network to monitor the environmental conditions of the library in real-time. The application is designed to assist library managers in improving operational efficiency and facility management, as well as enhancing user experience. The System Usability Scale (SUS) method is employed to evaluate the usability of the application. Literature review is conducted to understand the context of implementing SUS, while user interface design is carried out through wireframing and high-fidelity design. Usability testing is conducted using SUS questionnaires distributed to respondents. The research findings indicate that the LibrarySense application achieves an average SUS score of 81.74, indicating a high level of user satisfaction with usability and user experience. This suggests that the LibrarySense application has the potential to enhance the quality of the library environment and support managers in making more informed decisions.